Development of self-efficacy scale of differentiated instruction for teachers - Yilmaz, Rumeysa; Bal, Ayten Pinar; Atas, Vildan (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2022)
The purpose of this research is to develop a scale to determine teachers' self-efficacy levels regarding differentiated instruction. To create the item pool, the first 61 item draft form was prepared. This draft form was submitted to the opinion of experts from different fields and necessary corrections were made. Before starting the analysis process, the data were numbered and transferred to the computer environment. Persons to participate in the study were selected by simple random sampling. The sample of the research consists of 572 teachers. During the analysis of the data, exploratory factor analysis and confirmatory factor analysis were performed. As a result of the exploratory factor analysis, it was seen that the scale consisted of 27 items and six factors. The factors of the scale are named